Depiction of the episode of Panch Pir coming to greet Jinadatta Suri - Temples of India Project Team (Jio Institute, 2024)
The second oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) is the episode of Panch Pir coming to greet Jinadatta Suri. The story is closely associated with Jinachandra Suri, who subdued five pirs (spiritual guides) who stood at the confluence of five rivers upon the request of Emperor Akbar. The painting depicts five human figures in five streams of water, approaching to pay their respects to the acharya (those who impart knowledge). On the banks, devotees are shown sitting with offerings. The inscription reads, ‘panch pir shri Jina datta suri ji.’